A Comparative Study of Job Satisfaction in Primary School Teachers of Government and Private School in District Patna, Bihar (International Journal of Innovative Research in Engineering & Management, 2022)
The researchers have found that the role  of teachers in the teaching learning process is very  important. Updated curriculum, advance books, tech  enabled class room may fail in the absence of a committed  teacher. The researchers have believed that a study on  teachers will be very meaningful for improving the  teaching learning processes. But there are several aspects  related with teachers that contribute to the teaching  learning process. The researcher, in the present research  paper, have detailed Job satisfaction issues related with  teachers and teaching learning process in India. A  comparison among the private school teachers and  government school teachers suggested that there is higher  level of Job satisfaction among the teachers in government  schools.
Keywords: Job satisfaction; Teaching Learning Process; Teachers’ Commitment